Caracterización de los auditores de sistemas de gestión pertenecientes a empresas certificadoras en Chile (2018)
In the current globalized market, companies must permanently improve their competitiveness and sustainability, such as the implementation and certification of management systems. Certification bodies have and hire auditors according to established requirements and who add value to the organizations they audit. However, this does not ensure that auditors comply with all the guidelines of an audit process to a management system, among multiple variables. The object of this article is to describe the competence profiles of the auditors of certification bodies. A study was carried out with a quantitative approach and a descriptive design of the relevant variables that define the competences of the auditors who perform the third-party audits to management systems. 20 auditors participated who have worked in important certification bodies in Chile. Different profiles of management system auditors were obtained based on their education, experience and training. It is concluded that there is a progression of the professional development of the auditors, starting with implementations and internal audit of management systems, later as consultants in implementations, audits and reporting. And as a final step, the performance as auditors of certification bodies and course rapporteurs.